Análise espaço-temporal da mortalidade por suicídio no Rio Grande do Norte no período de 2000 a 2015 - Santos, Emelynne Gabrielly de Oliveira (2017)
Suicide is one of the most pervasive types of violent deaths in the world, and despite the diffusion of programs to prevent this condition in Brazil, the mortality situation in this country is worrying, especially in some regions where there is an increase in percentage of deaths. The objective of this study was to analyze the spatio-temporal distribution of mortality by suicide in the State of Rio Grande do Norte from 2000 to 2015. This is a mixed ecological study that evaluated the suicide deaths recorded in Rio Grande do Norte , occurring in the period from January 1, 2000 to December 31, 2015. Death data were obtained from the Mortality Information System, and population information was obtained from the Brazilian Institute of Geography and Statistics. Spatial analysis was performed using crude rates, standardized rates and rates by Bayesian estimators. The univariate analysis was performed using the Moran Global and Local Index to evaluate the intensity and significance of the spatial clusters using the Terraview 4.2 software. The spatial bivariate analysis was performed by crossing the sociodemographic variables with mortality rates standardized by suicide using GeoDa software 1.6.1. The Potential Years of Lost Life were also calculated throughout the historical series. The regression regression with standardized rates (world population) was used to estimate the Annual Percentage Change, the 95% confidence interval and the inflection points of the curve, in order to verify the suicide mortality trend in Rio Grande using the Joinpoint 4.5.0 software. The classical statistical analysis was applied to evaluate the correlation between the variables of the study and for that the software SPSS 23.0 was used. There were 2,266 deaths from suicide from 2000 to 2015, with the ratio between the sexes being 5: 1 in the last year. Spatial analysis showed poor spatial autocorrelation for the Standardized Mortality Rates for both sexes, with formation of spatial clusters in the Seridó Region, mainly for males. The bivariate analysis showed the formation of clusters in the Seridó Region with the HDI and Aging variables. Bayesian estimators showed a homogenization of mortality rates, especially in municipalities with small population groups. 6,3582.5 potential years of life were lost throughout the historical series. In addition, there was a trend of increased male mortality up to 2003, followed by a period of stability. For females, the trend was for stability. The analysis of variance also pointed to the absence of statistically significant differences between PMT and the size of municipalities and health regions for most of the study years. It is concluded that the mortality due to suicide in the NB is unequally distributed in the territory, being associated spatially to the areas with the best socioeconomic indicators. There is no significant trend of increase, however the differences between the regions of the state and according to the size of the municipalities increased during the historical series.